Programming Teaching using Arduino and TinkerCad Circuits - Proposal of a Lesson Sequence - Fabro, João Alberto; Cordeiro, André Cristiano; Bim, Silvia Amelia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This paper presents a lesson sequence to teach programming using the Arduino platform and the free TinkerCad Circuits environment, promoting hands-on activities. The sequence supports block-based and C-like coding, enabling students to learn core programming concepts through online simulations or physical hardware. Freely available materials, including circuit designs and video lessons, support the approach. The sequence was applied in two distinct scenarios: a Multiuser Massive Online Course and in ten freshmen engineering courses of programming. Both experiences are described in the text, focusing on learning outcomes, engagement, and challenges. The main contribution of this work is the presentation of a set of free multimedia course material, together with a flexible, accessible framework for programming education focused on young adults, using a free simulation tool.